Left atrial functional remodeling assessed by echocardiography in patients undergoing ablation for atrial fibrillation: correlation with the presence of fibrosis and invasive atrial pressure. (4th February 2022) - Dal Porto, M; Dematte", C; Maines, M; Giovanelli, C; Vinco, G; Setti, E; Cemin, C; Rossi, A; Benfari, G; Fezzi, S; Catanzariti, D; Ribichini, FL; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Radiofrequency catheter ablation of pulmonary veins has become a common procedure for treatment of atrial fibrillation (AF). Nevertheless, the procedure is characterized by an extremely variable success rate, which reflects a great heterogeneity of factors implicated in AF recurrence and AF burden. Purpose: We focused on the role of left atrium (LA) in patients with paroxysmal and persistent AF who underwent catheter pulmonary veins ablation procedure. In particular we paid attention to three factors: echocardiographic evaluation of LA function, LA scar evaluated by electroanatomic mapping and LA pressures (LAP) during ablation procedure. The aim of the study was to investigate the correlation between echocardiographic parameters indicating atrial dysfunction (LA volume indexed, E/E', LAA contraction velocity, LA stiffness and LA longitudinal strain during reservoir phase (LASr)) and intraprocedural parameters (such as LAPpeak and the amount of fibrosis). Methods:  The study included 25 patients; mean age was 63 ± 8 years; nineteen patients (76%) had paroxysmal AF, eighteen patients (72%) were in sinus rhythm at the time of ablation. The population was divided into two subgroups according to the amount of fibrosis evaluated by electroanatomic mapping: patients with fibrosis ≥ 5% of the total LA volume were considered as having an atrial scar. All patients underwent a comprehensive transthoracic echocardiography and a transesophageal echocardiography before the ablation procedure. Intraprocedural data regarding LAPpeak and electroanatomic mapping were collected. Measurements were acquired during both sinus rhythm (SR) and AF. Results: Patients with atrial scar had similar LA volume compared to patients without scar (44  ml vs 37.4 ml, p = 0.108), but presented a trend towards higher LAPpeak (24.3 mmHg vs 15.9 mmHg, p = 0.053) and had higher E/E' (11 vs 7, p = 0.037) and consequently increased LA stiffness (0.72 vs 0.23, p= 0.006). Still, they had lower LASr  (16.6% vs 33.2%, p = 0.013) and tended to have reduced LAA contraction velocity (0.4 m/sec vs 0.7 m/sec, p= 0.005). Conclusions: The present findings suggest that functional remodeling of the LA, more than morphological changes, are correlated with the presence of atrial fibrosis and elevated atrial pressure detected during ablation procedures. These parameters may represent potential criteria to guide patients' selection for ablation procedure and deserve dedicated studies to be confirmed.